If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14y-75=16y-91
We move all terms to the left:
14y-75-(16y-91)=0
We get rid of parentheses
14y-16y+91-75=0
We add all the numbers together, and all the variables
-2y+16=0
We move all terms containing y to the left, all other terms to the right
-2y=-16
y=-16/-2
y=+8
| 3p=p+76 | | P+2=3p | | n×9÷3×25=40 | | Y=-1.5x2-3 | | 3y-1=y+97=6y-8=2y+20 | | 5t+80/3t=3 | | 13x+29=5x+125 | | 4x+6=-6x | | 12y2+y-25=0 | | y5=2 | | .015x=15 | | 5x-20=-2+15 | | (x+1)^12=1,168 | | 0=-4(x-10)(x-90) | | 3x=2+ | | 8x+5=4x+6=5x-1 | | 7^{4x-8}=11^{2x+10} | | 5^(4x+1)=4^(3x+2) | | 5a+29=10 | | 3n+(-13)=17 | | 10x+21=15-22x | | -13=15+d | | (-2x)=(5-3x) | | 4x+9x-4=1 | | 4x+9x-3=1 | | 9a=45+5 | | 18=2x–14 | | 10x+9x=25 | | 4x+20=0-x | | (82)/(2x)=4 | | 4x=2=6x-8 | | 7p+20=13 |